PENGARUH KUALITAS AUDIT DAN LEVERAGE TERHADAP MANAJEMEN LABA DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI - Arvitha Dinda Rosena; Susi Dwi Mulyani; Bambang Prayogo (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2016)
This study used one research model to obtain empirical evidence about the effedts of audit quality and debt covenant on earning management with firm size as moderation variable. Variables used in this research model are audit quality, debt covenant, firm size and earnings management.Sampel on this research is manufacture company listed in Bursa Efek Indonesia for period 2012 – 2015. Based on purposive sampling, sampel that used for this research is 71 company with four year period, so there ar 284 samples. Analysis data method that used for this research is SPSS version 17, with a value of significance was set at 5%.The result of the research concludes that the audit quality does not have an negative effect to earnings management. Meanwhile, leverage have a negative significant effect to earnings management. This research also concludes if firm size is not meoderate the negative effect of audit quality to earning managements. However, firm size is moderating the positive effect of leverage to earning management.